High Serum miR-19a Levels Are Associated with Inflammatory Breast Cancer and Are Predictive of Favorable Clinical Outcome in Patients with Metastatic HER2(+) Inflammatory Breast Cancer - Anfossi, Simone (Public Library of Science, 2014)
INTRODUCTION: Altered serum microRNA (miRNA) levels may be correlated with a dysregulated expression pattern in parental tumor tissue and reflect the clinical evolution of disease. The overexpression of miR-21, miR-10b, and miR-19a is associated with the acquisition of malignant characteristics (increased tumor cell proliferation, migration, invasion, dissemination, and metastasis); thus, we determined their utility as serum biomarkers for aggressive breast cancer (HER2-overexpressed or -amplified [HER2(+)] and inflammatory breast cancer [IBC]). EXPERIMENTAL DESIGN: In this prospective study, we measured miR-21, miR-10b, and miR-19a levels using quantitative reverse transcriptase-polymerase chain reaction in the serum of 113 breast cancer patients and determined their association with clinicopathologic factors and clinical outcome. Thirty healthy donors with no history of cancer were enrolled as controls. RESULTS: Patients with non-metastatic HER2(+) breast cancer had higher serum miR-21 median levels than patients with non-metastatic HER2(−) disease (p = 0.044); whereas patients with metastatic HER2(+) breast cancer had higher serum miR-10b median levels than patients with metastatic HER2(−) disease (p = 0.0004). There were no significant differences in serum miR-19a median levels between HER2(+) and HER2(−) groups, regardless of the presence of metastases. High serum miR-19a levels were associated with IBC (p = 0.039). Patients with metastatic IBC had significantly higher serum miR-19a median levels than patients with metastatic non-IBC (p = 0.019). Finally, high serum miR-19a levels were associated with longer progression-free survival time (10.3 vs. 3.2 months; p = 0.022) and longer overall survival time (median not reached vs. 11.2 months; p = 0.003) in patients with metastatic HER2(+) IBC. CONCLUSION: High levels of miR-21 and miR-10b were present in the serum of patients with non-metastatic and metastatic HER2(+) breast cancer, respectively. High levels of serum miR-19a may represent a biomarker for IBC that is predictive for favorable clinical outcome in patients with metastatic HER2(+) IBC.